Mapping the Pāśupata Landscape Narrative, Place, and the Śaiva Imaginary in Early Medieval North India - Cecil, Elizabeth A. (Gonda Indological Studies, 2020)
In Mapping the Pāśupata Landscape Elizabeth A. Cecil presents a spatial and material history of the Pāśupata tradition and examines the formation of a Śaiva religious landscape in Early Medieval India. Readership: All interested in the history of Hinduism, and particularly the worship of the god Śiva, in premodern India; scholars of early medieval history and society in South Asia, and those interested in the study of text and material culture.